Criação de um protocolo clínico odontológico baseado no levantamento epidemiológico do câncer de boca do hospital de oncologia de São Luís - MA - Souza, Ingrid Araujo de Oliveira (2011)
The incidence of oral cancer in Brazil is among the highest in the world. In this study we evaluated 164 handbook and 41 obituaries seeking information related to risk factors for its development, staging and therapeutic procedures used for diagnosis of lesions. We created a questionnaire with 13 questions related to oral cancer and applied to students of dentistry in the last period of two universities in order to evaluate the degree of knowledge of these future professionals in the face of a precancerous lesion. Based on the results of epidemiological view and questionnaire, we created a protocol for dental care so that there is effective participation of the dentist in oncology hospitals emphasizing the importance of these professional quality of the therapeutic results of oral cancer, thus mitigating their undesirable side effects and improving the quality of life of these patients.